Mechanical stability of intermediate moisture starch-glycerol systems - Enrione, Javier (2005)
There is conflicting information on the mechanical properties and ageing kinetics of starch-water-glycerol systems. This makes understanding the changes occurring on storage of edible products difficult to predict. The work described in this thesis looks at model systems consisting of thermomechanically extruded plasticized starches (waxy maize, rice and wheat) and commercial products. The objectives of the work were to evaluate how the presence of polyols effects glass transition temperature (Tg), sorption isotherms, diffusion rates and texture parameters and to create models that could be used to predict behaviour. Very similar results were obtained for the starch samples except that monolayer (ma) values were higher for the waxy maize starch than for the wheat and rice. The waxy maize also was more brittle at equivalent moisture content when compared to the other two starches. Glycerol had a major impact on the water absorption. For RHs > 70% more water absorbed up by samples containing glycerol while the opposite occurred at RHs <60%. Monolayer values for GAB and BET confirmed this finding. The behaviour could be predicted if an interaction factor <1 was used in weight fraction models. Tg of the samples was measured by DSC and also by using predictive models, where the ten-Brinke Karas equation was found to give the best predictions. A value that was found to be most beneficial for the prediction of retrogradation was (storage temperature minus Tg). Change in texture was associate with (T-Tg), although the brittle ductile transition occurred 40°C below T-Tg=O. Diffusivity values increased with plasticizer level up to 8*10 3 m'z/s. There was an apparent fall in values when the samples were above Tg. However, it is suggested that this is due to sample geometry change rather than a change in diffusion mechanism. The Tg values also were found to be a good predictor of the type of change occurring in the model systems and food products during storage. Below Tg physical aging (enthalpy relaxtion) could be seen in the samples and retrogradation of the starch occurred above Tg. The rates of retrogradation were not affected by glycerol content directly and knowledge of Tg and storage temperature were sufficient to predict the retrogradation. Products became stiffer on storage and this was associated with molecular reassociation of the starchy component, but control of the moisture was also critical as water still dominated product behaviour even in the presence of glycerol.